2011
DOI: 10.1103/physrevd.84.124021
|View full text |Cite
|
Sign up to set email alerts
|

2+1dimensional magnetically charged solutions in Einstein-power-Maxwell theory

Abstract: We obtain a class of magnetically charged solutions in 2 þ 1 dimensional Einstein-Power-Maxwell theory. In the linear Maxwell limit, such horizonless solutions are known to exist. We show that in 3D geometry, black hole solutions with magnetic charge do not exist even if it is sourced by the powerMaxwell field. Physical properties of the solution with particular power k of the Maxwell field is investigated. The true timelike naked curvature singularity develops when k > 1 which constitutes one of the striking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
(40 reference statements)
0
38
0
Order By: Relevance
“…In the first paper of Hassaïne and Martínez [9][10][11][12][13][14][15][16][17][18][19][20][21][22] it was shown that the action given in (1) is conformally invariant if k = 3 4 . In this section we set k = 3 4 and = 0 so that the following solution is obtained for the field equations (14)- (16):…”
Section: A Brief Account For a Conformally Invariant Maxwell Source Wmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first paper of Hassaïne and Martínez [9][10][11][12][13][14][15][16][17][18][19][20][21][22] it was shown that the action given in (1) is conformally invariant if k = 3 4 . In this section we set k = 3 4 and = 0 so that the following solution is obtained for the field equations (14)- (16):…”
Section: A Brief Account For a Conformally Invariant Maxwell Source Wmentioning
confidence: 99%
“…F μν F μν , where, as usual, the field tensor is defined by F μν = ∂ μ A ν − ∂ ν A μ . This Lagrangian belongs to the class of NED with k-power law Maxwell invariant F μν F μν k [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A similar Lagrangian in 3 + 1 dimensions with magnetic field source has been considered in [23][24][25], and with an electric field as well as both electric and magnetic fields in [26].…”
Section: Introductionmentioning
confidence: 99%
“…Besides sourced by a mass and a negative cosmological constant, pure BTZ black holes can be also to added new sources such as electric/magnetic fields from Maxwell's theory [23][24][25], Maxwell-dilaton [26], rotation [27], perfect fluid [28,29] and others [30,31]. It is interesting to note that the nonlinear electrodynamics (NED) is useful to overcome to eliminate the electromagnetic singularities due to point charges that occur in the linear Maxwell theory.…”
Section: Introductionmentioning
confidence: 99%
“…The interest started all with the discovery of a 2 + 1-dimensional black hole solution by Banados, Teitelboin and Zanelli (BTZ) [1][2][3][4]. The physical source of the BTZ black hole was a cosmological constant, which was subsequently extended with the presence of different sources [5][6][7][8][9][10][11][12][13][14][15][16][17]. How significant are these sources physically?…”
Section: Introductionmentioning
confidence: 99%